Calcium and boron supplementary effect on cassava performance in a sandy Typic Paleustult - Roongnapa Bowichean; Suphicha Thanachit; Somchai Anusontpornperm; Richard William Bell (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science)
Calcium (Ca) and boron (B) interactions are crucial for nutrition and crop performance, but information is scarce for cassava. Cassava’s yield response to Ca and B was investigated in an acidic sandy soil, using a split-plot design. The main plot comprised 0, 50, 200 and 400 kg ha−1 of net Ca soil application with the subplot containing 0, 1 and 2 kg net B ha−1. Boron was applied as single soil, foliar, and equally split soil and foliar applications. The sole B overall was superior to sole Ca in enhancing cassava growth. The combined 400 kg Ca ha−1 and 1 kg B ha−1 soil addition significantly promoted the highest fresh tuber yield and starch yield whereas adding just 200 kg Ca ha−1 gave the lowest yields but these yields increased significantly with supplemented B. Ignoring B rates, the single B foliar application was the least effective. Calcium and B interactively stimulated more uptake of plant nutrients, but the Ca concentration was lowered significantly when B was added. The findings signified a vital impact of Ca combined with B on increasing cassava yield despite B having a slightly antagonistic effect on accumulated-Ca in cassava.